Bibliometric Analysis: Augmented Reality in Science Education Research Trends - Parham Sa’adi; Misbah; Rossy Arlinda; Muhdi Harto; Nurlaela Muhammad (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze research trends related to the topic of Augmented Reality in 2019-2023* through bibliometric analysis with the Scopus database. Based on the criteria, 490 articles were obtained from 3906 documents. These articles have been translated from international journals indexed by Scopus. The selection references were then managed using reference management software, namely Mendeley. After working on the database, the researchers classified and visualized it using VOSviewer software. The results show that Augmented Reality research is gradually increasing every year. The United States and Germany contribute the most research globally. Visualizing Augmented Reality research trends for 2019-2023*, there are six clusters. The results of this research can support researchers regarding Augmented Reality research trends in the world and provide direction for further research. Overall, these reflections provide an excellent reference point for further research on Augmented Reality.